A comparison of formal and informal methods for assessing language and cognition in children with Rett syndrome. (July 2021) - Ward, Callie; Chiat, Shula; Townend, Gillian S.
Highlights: Children with RTT demonstrate a broad range of cognitive ability. Combining formal and informal assessment tasks yields better quality information. Some children with RTT respond better on informal assessments, others on formal. All assessments must be adapted to meet an individual's physical constraints. It is vital that hidden cognitive abilities are uncovered and supported. Abstract: Background: Opinions about the cognitive and receptive language skills of people with Rett syndrome (RTT) range from severe intellectual impairment to near-normal development. Assessment is challenging because most are non-verbal, with no purposeful hand use. Clarkson et al. (2017) adapted the Mullen Scales of Early Learning for use with eye gaze technology (MSEL-A/ET) for people with RTT. Aims: To investigate and compare the performance of children with RTT on formal and newly-designed informal assessments of language and cognition using eye gaze/tracking technology. Methods and procedures: Ten children with RTT aged 4:0–6:8 were assessed on the MSEL-A/ET for Visual Reception (VR) and Receptive Language (RL), and standard MSEL for Expressive Language (EL). Informal assessments of the same skills were embedded in activities such as reading and cake-decorating. Outcomes and results: Standard scores on MSEL-A/ET VR and RL subtests ranged from 'very low' to 'above average'. All children scored 'very low' on standard EL assessment. Informal assessments added information about EL, with children producing 1–3 word utterances and a range of communicative functions through an eye gaze device. Conclusions and implications: Combining low-tech augmentative and alternative communication, eye gaze technology, informal activities and formal assessment, yields greater insight into children's abilities. This is important in informing suitable support and education for the individual.